Can We Have More Butter and Guns Simultaneously? An Endogeneity Perspective - Rafał Woźniak; Jacek Lewkowicz (Gospodarka Narodowa. The Polish Journal of Economics, 2023)
Drivers and outcomes of military expenditures are an important topic in geopolitics and public debate. It is often argued that increases in the military budget can boost the economy through extended military equipment production. What should then be noticeable is a feedback relationship between military expenditures and the current state of the economy. This paper investigates this reverse relationship at the macro level using an unbalanced panel dataset of 173 countries over the period 1949–2020. Our empirical analysis implies that the claimed positive feedback loop between military expenditures and economic growth is either completely absent or, at most, very weak.